Reframing Pastoral Practices of Bofedal Management to Increase the Resilience of Andean Water Towers - Karina Yager; Manuel Prieto; Rosa Isela Meneses (Mountain Research and Development, 2021)
Across the Andes, a critical challenge for mountain socioecological systems is securing water for future generations. Pastoral communities are especially vulnerable because their livelihood practices are often unseen or perceived as a threat to natural resource conservation. In addition to the challenges of climate change, socioeconomic and political processes complicate the drivers of pasture degradation and sustainable water management. Often overlooked systems in assessments of Andean water towers are bofedales (high-altitude peat wetlands), which are critical to supporting mountain pastoral livelihoods. While “natural” azonal mountain peatland and humid meadow development occurs across the Andes, we posit that bofedales are sociohydrological systems created through pastoral management practices over generations. Drawing on the results of applied research on bofedales across the Andes and a literature review of published papers, we present a conceptual reframing of bofedal typologies and change analysis, which prioritizes the role of pastoralists in interdisciplinary research and comparative assessments of land-use and land-cover change in Andean highland regions. We identified key socioecological challenges to sustainable bofedal management, related to herder decision-making and articulated within broader socioeconomic processes. Reframing bofedales as sociohydrological constructs permits the identification of actionable knowledge and the support of water conservation practices applied by pastoralists across Andean water tower regions. If Andean pastoralists are recognized as stewards of sociohydrological systems that are critical to water towers, rather than perceived as threats to natural resources, bofedal conservation planning may be prioritized and locally supported.